Yellow fever vaccine 17D administered to healthy women aged between 40 and 54 years halves breast cancer risk: an observational study. Issue 4 (July 2018) - Mastrangelo, Giuseppe; Pavanello, Sofia; Fadda, Emanuela; Buja, Alessandra; Fedeli, Ugo
Abstract : Transcripts of human endogenous retrovirus K are expressed in most breast cancers (BCs). Yellow fever vaccine 17D (YFV) expresses a protein with a closely homologous epitope. Cross-reactive immunity could hypothetically inhibit BC growth at least in women aged around 50 years at diagnosis, in whom the prognosis of BC was found to be better than that in women younger or older. A cohort of 12 804 women who received YFV in the Veneto Region, Italy, was divided into two subcohorts according to age at vaccination and followed up through the Veneto Tumor Registry. The time since vaccination until cancer incidence was categorized (⩽1.9; 2–3.9; 4–5.9; 6–7.9; 8–10.9; ≥11 years) and, using the lowest class as a reference, the incidence rate ratio for BC with a 95% confidence interval and P -value was estimated by Poisson regression in each time since vaccination class, adjusting for age and calendar period. In 3140 women vaccinated at 40–54 years of age, YFV administration resulted in a protective effect of long duration slowly fading over time with a U-shaped pattern of response. Overall, BC risk was reduced by about 50% (incidence rate ratio=0.46; 95% confidence interval=0.26–0.83; P =0.009) 2 years after vaccination. Cross-reactive antigens could not be the mechanism because no protection was observed in women vaccinated before 40 or after 54 years of age. BC cells in a microscopic stage of disease can be destroyed or severely damaged by YFV if BC is not very aggressive. To prove that treatment is truly effective, a placebo-controlled double-blind trial should be conducted.